EVALUATION OF MORPHOMETRIC PARAMETERS OF SPLEEN DEVELOPMENT IN RATS DURING EARLY POSTNATAL ONTOGENESIS - Umarova Z.Kh., Azizova F.Kh., (Central Asian Journal of Medicine, 2025)
This article examines the characteristics of morphometric changes in the main structures of the spleen in white rats during early postnatal ontogenesis in the course of development. It reveals the patterns of formation of various structural and functional zones of this organ at different stages of early postnatal ontogenesis. It has been established that during postnatal ontogenesis, the morphological and morphometric parameters of the functional zones of the spleen in white rats undergo significant changes, which are reflected in different age-related aspects.